2011
DOI: 10.1097/scs.0b013e31822e5ebf
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Three-Dimensional Philtral Morphology

Abstract: This study was designed to evaluate detailed philtral morphology involving sex and racial differences and to clarify the objective parameters related to subjective judgments regarding the clarity of the philtrum. Fifty-five Japanese and 20 Mexican normal subjects aged 24 to 40 years were recruited, and three-dimensional facial data were acquired using a noncontacting optical surface scanner. The visual classification of the philtral column morphology in Japanese adults using facial photographs revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…However, previous studies classified the philtral shape of Japanese young adults into four types by visual observation: parallel, triangular, concave, and unclear. 22,23 Although this classification may appear to provide a simple understanding of the types of the philtrum, accurate criteria that distinguish the several types of philtrum are necessary to avoid arbitrary surgery of surgeons. In one study, the parallel type was defined when the philtral columns were "approximately" parallel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous studies classified the philtral shape of Japanese young adults into four types by visual observation: parallel, triangular, concave, and unclear. 22,23 Although this classification may appear to provide a simple understanding of the types of the philtrum, accurate criteria that distinguish the several types of philtrum are necessary to avoid arbitrary surgery of surgeons. In one study, the parallel type was defined when the philtral columns were "approximately" parallel.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the parallel type was defined when the philtral columns were "approximately" parallel. 23 However, this approximation could be interpreted considerably differently among researchers. They also reported that there was a sex difference in the predominant type, and the shape of philtrum in male was a stronger impression than in female.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great body of work in facial anthropometry is that of Farkas, who established a database of norms that are well accepted as linear, angular, and surface contour reference values [9, 17]. Other reference values are from 2D cephalometric and photographic assessments [13, 1821]. More recently, the laser scanning technique, the contact-type 3-dimensional measurement technique using facial plaster models, and the measurement technique using 3-dimensional computed tomography are considered to be able to 3- dimensionally measure the complicated shape of the face and to produce images on a computer screen [13, 20, 22].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics and differences of the shapes of the nostrils have been studied in several racial groups [1315, 18, 21, 25, 26]. Among the classifications of nostrils, Farkas' classification divides the shape of nostrils by the angle between the right and left long nostril axes [25].…”
Section: Discussionmentioning
confidence: 99%